Alburnus zagrosensis, a junior synonym of Alburnus sellal (Teleostei: Leuciscidae) - Eagderi, Soheil; Nikmehr, Nasrin; Freyhof, Jörg (Zootaxa, 2019)
Morphometric, meristic and molecular (COI) characters of Alburnus zagrosensis, from the upper Karun River drainage in Iran, largely overlap or are identical with those of A. sellal, a species widely distributed in the Qweik River and the Persian Gulf basin, including the Karun River drainage. As no character states could be found to clearly distinguish these species, A. zagrosensis should be treated as a junior synonym of A. sellal.